The Drosophila ncd microtubule motor protein is spindle-associated in meiotic and mitotic cells. - Hatsumi, M.; Endow, S.A. (Journal of Cell Science, 1992)
The nonclaret disjunctional (ncd) protein is required for normal chromosome distribution in oocytes and early embryos. Mutants of ncd cause frequent nondisjunction and loss of chromosomes, suggesting a role for the protein in spindle function or chromosome movement in meiosis and early mitosis. The ncd protein contains a region of predicted sequence similarity to the microtubule motor protein, kinesin. In vitro motility assays have demonstrated that ncd is a motor that unexpectedly moves toward the minus ends of microtubules, opposite to the direction of kinesin movement. Using antibodies directed against nonconserved regions of the protein, we have localized the ncd motor protein to the meiotic and early mitotic spindle, and to spindles in a mitotically dividing cultured cell line. Its presence in the spindle of meiotic and mitotic cells implies a role for the protein as a spindle motor. The motor may play an essential role in establishing spindle bipolarity in meiosis.